Body Composition Indicators and Cardiovascular Health Score among Young Adults: An Early Cardiovascular Aging Perspective - Rayhani Ichsan; Nurul Mufidah Damry; Nurul Mutiah Aminuddin; Aida Ayu Chandrawati; Bhirau Wilaksono; Okto Sofyan (PT ARRUS Intelektual Indonesia, 2026)
This study examined the association between body composition indicators and cardiovascular health score among young adults from an early cardiovascular aging perspective. A cross-sectional analytic study was conducted using de-identified data from 44 young adults, consisting of 35 females and 9 males. Body composition indicators included body mass index, waist circumference, body fat percentage, skeletal muscle percentage, and visceral fat index. Cardiovascular and metabolic markers included systolic blood pressure, diastolic blood pressure, total cholesterol, and random blood glucose. Cardiovascular health was assessed using a modified Life’s Essential 8-based cardiovascular health score. Spearman correlation and age- and sex-adjusted linear regression analyses were performed. Higher adiposity indicators were significantly associated with lower cardiovascular health score, including body mass index, waist circumference, body fat percentage, and visceral fat index. Visceral fat index showed the strongest inverse association with cardiovascular health score. In contrast, skeletal muscle percentage was positively associated with cardiovascular health score. Adiposity indicators were also associated with less favorable blood pressure profiles, particularly systolic blood pressure. These findings suggest that body composition indicators, especially visceral fat index and skeletal muscle percentage, may provide practical insight into early cardiovascular health variation among young adults.